Предмет: Математика,
автор: Санька777
Помогите!!!!!!!!!!!!!!!!!!!!
Приложения:
Ответы
Автор ответа:
0
{2x-y=-1 ⇔ 2x=-1+y ⇔ x = (y-1)/2 ⇔ x=1/2 *(y-1) ⇔ x=0.5(y-1)
{y²-4x-2 = 0
y² - 4*0.5(y-1) - 2 = 0
y² - 2(y-1) - 2 = 0
y² - 2y + 2 - 2 = 0
y² - 2y = 0
y(y-2) = 0
y₁ = 0
y-2=0
y₂ = 2
x₁= 0.5(0-1)=0,5*(-1)
x₁ = -0,5
x₂ = 0.5 (2-1) = 0,5*1
x₂ = 0.5
Ответ: (-0,5 ;0) , (0,5 ; 2)
{y²-4x-2 = 0
y² - 4*0.5(y-1) - 2 = 0
y² - 2(y-1) - 2 = 0
y² - 2y + 2 - 2 = 0
y² - 2y = 0
y(y-2) = 0
y₁ = 0
y-2=0
y₂ = 2
x₁= 0.5(0-1)=0,5*(-1)
x₁ = -0,5
x₂ = 0.5 (2-1) = 0,5*1
x₂ = 0.5
Ответ: (-0,5 ;0) , (0,5 ; 2)
Похожие вопросы
Предмет: Информатика,
автор: ruhshona770
Предмет: Математика,
автор: konovalovamaria
Предмет: Русский язык,
автор: Katyaof
Предмет: Литература,
автор: ivanovaaaaaaaaaa
Предмет: История,
автор: ПолинаС1